Calcium-fortified fresh milk ameliorates postmenopausal osteoporosis via regulation of bone metabolism and gut microbiota in ovariectomized rats - Qishan Wang; Bin Liu; Xianping Li; Junying Zhao; Zongshen Zhang; Weicang Qiao; Xinyue Wei; Lijun Chen (Food Science and Human Wellness)
The aging of the global population has made postmenopausal osteoporosis prevention essential; however, pharmacological treatments are limited. Herein, we evaluate the effect of calcium-fortified fresh milk (FM) in ameliorating postmenopausal osteoporosis in a rat model established using bilateral ovariectomy. After 3 months of FM (containing vitamin D, and casein phosphopeptides, 1000 mg Ca/100 g) or control milk (110 mg Ca/100 g milk) supplementation, bone changes were assessed using dual-energy X-ray absorptiometry, microcomputed tomography, and bone biomechanical testing. The results revealed that FM can regulate bone metabolism and gut microbiota composition, which act on bone metabolism through pathways associated with steroid hormone biosynthesis, relaxin signaling, serotonergic synapse, and unsaturated fatty acid biosynthesis. Furthermore, FM administration signif icantly increased bone mineral content and density in the lumbar spine and femur, as well as femoral compressive strength, while improving femoral trabecular bone parameters and microarchitecture. Mechanistically, we found that the effects may be due to increased levels of estrogen, bone formation marker osteocalcin, and procollagen type Ⅰ N-propeptide, and decreased expression of the bone resorption marker C-telopeptide and tartrate-resistant acid phosphatase 5b. Overall, the f indings suggest that FM is a potential alternative therapeutic option for ameliorating postmenopausal osteoporosis.